Vernal keratoconjunctivitis in an Israeli group of patients and its treatment with sodium cromoglycate. Issue 2 (February 1982) - Baryishak, Y R; Zavaro, A; Monselise, M; Samra, Z; Sompolinsky, D
Abstract : Vernal keratoconjunctivitis (VKC) is usually considered as an allergic eye disorder of type I, and in most therapeutic trials it has been shown to yield to topical treatment with sodium cromoglycate. This has been confirmed in the present study of VKC patients from Israel. However, some of the cases seemed not to benefit from this treatment. In a survey of IgE levels in VKC patients in Israel tear IgE levels were significantly increased in 63.5%, but in 29% of the patients both tear and blood IgE levels were normal to low. The possibility that some of the cases diagnosed as VKC might have another cause than IgE-mediated atopy is discussed.